Efflorescence - Abloh, Virgil 1980-2021 (Innen, 2019)
A pamphlet consisting of photographs documenting Efflourescence, a furniture collection designed in 2019 by Virgil Abloh for Galerie kreo, which takes its cues from brutalism and the urban landscape. Described by Abloh as being positioned somewhere between sculpture and useful object, each piece is formed from concrete and features a punctured surface